Islamic Dakwah in the Digital Era: A Systematic Literature Review of Habib Husein Jafar Al Hadar - Sari Nopalisa Putri; Syaiful Bahri (Maddah: Journal of Advanced Da'wah Management Research, 2026)
Modern information technology and mass education have not weakened traditional religious authority; instead, they have compelled these authorities to adapt to remain relevant within society. This study aims to examine the strategies of popular culture adaptation in the digital dakwah narratives of Habib Husein Jafar Al Hadar on social media. The research employs a qualitative method with a descriptive-analytical approach to deeply examine digital content and audience engagement. The results of this study conclude that the popular culture adaptation strategies implemented by Habib Husein Jafar Al Hadar are manifested in three primary forms: the use of inclusive slang, the adoption of Japanese subculture aesthetics, and the visualization of dakwah through the medium of modern comics. These findings explicitly address the research objectives by demonstrating that the hybridization of tradition and contemporary trends is not merely an attempt to follow current fads, but rather a reconstruction of traditional religious authority within the digital space. Through this mechanism, digital technology serves as a strategic opportunity for the 'Habib' figure to expand the reach of his dakwah and strengthen his spiritual influence amidst the shifting identity dynamics of the modern young Muslim generation, while simultaneously bridging the divide between sacred values and profane culture By integrating sacred traditions with popular trends, these figures successfully maintain their authority in a rapidly changing digital landscape. This study concludes that such adaptations are essential for religious messages to be effectively received without losing their core essence.